Polynomial algorithms for projecting a point onto a region defined by a linear constraint and box constraints in ℝn - Stefan M. Stefanov (Journal of Applied Mathematics)
We consider the problem of projecting a point onto a region defined by a linear equality or inequality constraint and two-sided bounds on the variables. Such problems are interesting because they arise in various practical problems and as subproblems of gradient-type methods for constrained optimization. Polynomial algorithms are proposed for solving these problems and their convergence is proved. Some examples and results of numerical experiments are presented.